(untitled) (Itinera, 2019)
This paper aims to report the conclusions of a practice-as-research laboratory carried out with students of Université Lumière Lyon 2, which took place within the project “Borders’ trespassing: from France to Italy, from research to creation, from an art to another”. Students were invited to write a dramaturgy inspired from Casanova’s life. They explored several questions about playwriting (action, character, dialog…) and found original solutions to write a biographic play. The results question the representation of identity and personality in our mediatic world, experimenting intermediality in their text. Keymords: théâtre, Giacomo Casanova, laboratoire, recherche-création, intermédialité.